Pengaruh Sistem Keuangan Desa dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Desa - Wardani, Qholba Ainun; Mustoffa, Ardyan Firdausi; Ardiana, Titin Eka (Universitas Muhammadiyah Semarang, 2022)
Ponorogo Regency, especially Babadan Subdistrict, is included in the villages that have yet to report the results of the APBDes report preparation. This is because, in Babadan Sub-district, there has been no application for non-siltap ADD distribution compared to other sub-districts. In addition, the competence of human resources still needs to improve, and regulations regarding the issuance of financial reports have yet to be issued. Still, the village has been required to draw up village regulations. This study aims to determine the effect of the Sistem Keuangan Desa, human resource competence, and internal control system either partially or simultaneously on the quality of village financial reports in the villages of Babadan Subdistrict, Ponorogo Regency. This research is quantitative research with primary data originating from questionnaires. The technique used in determining the sample is the saturated sampling technique. The number of samples in this study was 132 from 12 villages in Babadan District. The results of this study indicate that: (1) Sistem Keuangan Desa has a positive and significant effect on the quality of village financial reports, (2) human resource competence has a positive and significant effect on the quality of village financial reports, (3) the internal control system has a positive and significant effect on the quality of village financial reports, (4) Sistem Keuangan Desa, human resource competence, and internal control system simultaneously have a positive and significant effect on the quality of village financial reports.